Susie King Taylor : nurse, teacher & freedom fighter - Dunbar, Erica Armstrong; Buford, Candace; Taylor, Susie King, 1848-1912. (New York : Aladdin, 2023)
A groundbreaking figure in every sense of the word, Susie King Taylor (1848-1912) was one of the first Black nurses during the Civil War, tending to the wounded soldiers of the 1st South Carolina Volunteer Infantry Regiment. Afterward, she was a key figure in establishing a postbellum educational system for formerly bonded Black people, opening several dedicated schools in Georgia. Taylor was also one of the first Black women to publish her memoirs. Even as her country was at war with itself, Taylor valiantly fought for the rights of her people and demonstrated true heroism.--.
"Author of the National Book Award Finalist Never Caught"--Dust jacket.
Includes "Reminiscences of my life in camp" written by Susie King Taylor and published in Boston in 1902 (pages 179-271).
"We made the decision to write this book about Susie King Taylor's experiences in a first-person voice. Connecting the information given to us from her own narrative that she published in 1902, we have included additional experiences we imagine must have confronted her. In a few places, we needed to create first names to breathe life and dignity into the people who lived during this time. In some cases, we use "informed speculation" - meaning we tried to estimate what Taylor would have experienced - even though she may not have told us about her feelings in writing. Even so, this is a history book, and wherever possible, we use Susie King Taylor's own words"--page viii.
new kids book 2025 winter.
Ages 10 up.
Keywords: Taylor, Susie King, -- 1848-1912 -- Juvenile fiction; Taylor, Susie King, -- 1848-1912.; Taylor, Susie King, -- 1848-1912.; 1861-1865; African American nurses; African American teachers; African American nurses; African American teachers; African American; African American teachers; Nurses; Teachers; African Americans; African Americans; Nurses; Teachers; JUVENILE NONFICTION / Biography & Autobiography / Historical; JUVENILE NONFICTION / Biography & Autobiography / Women; JUVENILE NONFICTION / Diversity & Multicultural; African American nurses; African American teachers; Medical care; United States -- History -- Civil War, 1861-1865 -- Medical care -- Juvenile fiction; United States -- History -- Civil War, 1861-1865; United States; United States -- History -- Civil War, 1861-1865 -- Medical care; Fiction; History; Juvenile works; Historical fiction; Biographical fiction